PERLOCUTIONARY ACT PERFORMED IN JOHN WICK MOVIE - Ela Martisa; Ahmad Syaiful; Arman Arman; Amiruddin Eso (Program Studi Pendidikan Bahasa Inggris, 2023)
This study discussed the perlocutionary act performed in the John Wick movie based on the theory of Qiang. The aim of the study is to determine the types of perlocutionary acts used in the movie through the main character’s utterances. The descriptive-qualitative method was applied to the research method. Techniques of data collection were carried out by searching, downloading, reading, watching, and coding the data. Techniques of data analysis were conducted by presenting, describing, interpreting, and drawing conclusions. The findings of the study show that perlocutionary acts really exist in the movie and are applied by the main character in order to influence others. There were 11 pieces of data found, which included four types of perlocutionary acts used by John Wick as the main character in the movie. Perlocutionary act serves as the effect of utterances from the speaker to the hearer, intentionally or unintentionally. Among the four types of perlocutionary acts, type 1 is the most dominant type because the speaker's utterance can be clearly understood by the hearer so that the expected effect of the utterances can be realized. Keywords: movie, perlocutionary act, pragmatic.